Estimating Poisson's Ratio and Young's Modulus of the Outer Fruit Shell of Corn Grain - A. G. Pastukhov; S. F. Vol'vak (Сельскохозяйственные машины и технологии)
The paper highlights the need of reducing damage caused to corn grain during cobs threshing. The damage to the grain fruit shell can be eliminated by introducing limiting conditions and ensuring optimal parameters for the threshing and separating device operation. It has been confi rmed that the patterns of corn cobs threshing can be adequately described by applying the Hertzian elastic contact theory. (Research purpose) To obtain the Poisson's ratio and Young's modulus of the fruit shell of corn grain, whose surface is in direct contact with the working bodies of the threshing device. (Materials and methods) One-factor-ata- time experiments were conducted with the subsequent statistical processing of the data array. Poisson's ratio was experimentally studied for the fruit shell of dent corn and so was Young's modulus for the grain of fl int corn, dent corn, sugar corn and popcorn. (Results and discussion) Research methods and experimental equipment have been developed to determine the Poisson's ratio and Young's modulus of the fruit shell of corn grain. It was established that with a confi dence probability of 0.95, the average Poisson's ratio value of the fruit shell of the dent corn grain equals 0.356. Young's modulus was obtained by the following corn varieties: fl int corn – 98-125 megapascals, dent corn – 78-127 megapascals, sugar corn – 97-124 megapascals, popcorn – 127-169 megapascals. It was found out that the maximum permissible speed mode of threshing can be provided if the speed of contact interaction between the grain and the threshing device pin does not exceed 1.6 meters per second. (Conclusion). It was proved that for a more comprehensive application of the Hertzian elastic contact theory when modeling the processes of threshing corn cobs, it is necessary to know the Poisson's ratio and Young's modulus for the outer fruit shell of grain. The obtained numerical values of these mechanical and technological characteristics are recommended to be used in modeling the deformation processes that regulate the threshing speed regimes.